Crossing the Nuclear Envelope: Hierarchical Regulation of Nucleocytoplasmic Transport - Terry, Laura J; Shows, Eric B; Wente, Susan R (Science (American Association for the Advancement of Science), 2007)
Transport of macromolecules between the nucleus and cytoplasm is a critical cellular process for eukaryotes, and the machinery that mediates nucleocytoplasmic exchange is subject to multiple levels of control. Regulation is achieved by modulating the expression or function of single cargoes, transport receptors, or the transport channel. Each of these mechanisms has increasingly broad impacts on transport patterns and capacity, and this hierarchy of control directly affects gene expression, signal transduction, development, and disease.